ENHANCING PROGRAMS OF EDUCATION OFFICE THROUGH STRATEGIC PLANNING - Virgana Virgana (International Journal of Education, Information Technology, and Others, 2019)
A program planning with certain quality is needed to improve the provincial education district service to the community. This study aims to develop the district education office program in 2019 and guidelines for the provincial education service plan for the following year through strategic planning. This study uses a qualitative approach with SWOT analysis. Data collection is done through group interviews, plenary meetings and observations. Data obtained are grouped into components of strengths, weaknesses, opportunities, and threats, then analyzed into four strategic formulations, namely: Strengths - Opportunities (SO), Weaknesess - Opportunities (WO), Strengths - Treaths (ST), and Weaknesess - Treaths (WT). The results of the study were organizational positioning on strategic planning (W-T). The conclusion is that program planning arranged by positioning of strategic planning. We hope that the result of this study can be beneficial for the policy maker, stake holder, and other researchers in related field.